ELE restrains empty glumes from developing into lemmas - Hong, Lilan; Qian, Qian; Zhu, Keming; Tang, Ding; Huang, Zejun; Gao, Ling; Li, Ming; Gu, Minghong; Cheng, Zhukuan (Journal of genetics and genomics, 2010)
Although there is evident homology among reproductive organs when comparing Poaceae (grass) and eudicots, the identity of grass specific organs, such as lodicules, palea, lemma, and glumes has been the subject of a vast and largely inconclusive discussion. Here we provide some direct evidence to support the idea that the empty glumes of rice ( Oryza sativa) are counterparts of lemmas. We show that the development of empty glumes is regulated by ELE ( elongated empty glume ), which belongs to a plant specific novel gene family. Mutations at the ELE locus cause elongated empty glumes, which mimic the lemmas and have the epidermal morphology of lemmas with four or five vascular bundles. As a nuclear-localized gene, ELE is specifically expressed at the empty glumes of immature spikelets, and its ectopic expression causes many floral development defects, including lemma-like palea, extra palea-like structures, elongated lodicules, extra stamens and stigmas. Our result suggests that empty glumes are lemmas of the sterile florets located at the lateral side of the rice spikelet, and ELE acts as a regulator restraining its growth to maintain its small size in wild-type plants.